Business process re-engineering: a panacea for reducing operational cost in service organizations - Sungau, Joseph Joseph; Ndunguru, Philibert C. (Instituto Federal de Educaçã, 2024)
This article was published by Instituto Federal de Educaçã in the Independent Journal of Management & Production v. 6, n. 1, January - March 2015